Preliminary insights into the impact of dietary starch on the ciliate, Neobalantidium coli, in captive chimpanzees - Schovancová, Kateřina; Pomajbíková, Kateřina; Procházka, Petr; Modrý, David; Bolechová, Petra; Petrželková, Klára J (PloS one, 2013)
Infections caused by the intestinal ciliate Neobalantidium coli are asymptomatic in most hosts. In humans and captive African great apes clinical infections occasionally occur, manifested mainly by dysentery; however, factors responsible for development of clinical balantidiasis have not been fully clarified. We studied the effect of dietary starch on the intensities of infection by N. coli in two groups of captive chimpanzees. Adult chimpanzees infected by N. coli from the Hodonín Zoo and from the Brno Zoo, Czech Republic, were fed with a high starch diet (HSD) (average 14.7% of starch) for 14 days, followed by a five-day transition period and subsequently with a period of low starch diet (LoSD) (average 0.1% of starch) for another 14 days. We collected fecal samples during the last seven days of HSD and LoSD and fixed them in 10% formalin. We quantified trophozoites of N. coli using the FLOTAC method. The numbers of N. coli trophozoites were higher during the HSD (mean ± SD: 49.0 ± 134.7) than during the LoSD (3.5 ± 6.8). A generalized linear mixed-effects model revealed significantly lower numbers of the N. coli trophozoites in the feces during the LoSD period in comparison to the HSD period (treatment contrast LoSD vs. HSD: 2.7 ± 0.06 (SE), z = 47.7; p<<0.001). We conclude that our data provide a first indication that starch-rich diet might be responsible for high intensities of infection of N. coli in captive individuals and might predispose them for clinically manifested balantidiasis. We discuss the potential nutritional modifications to host diets that can be implemented in part to control N. coli infections.
Keywords: Ciliophora; Female; škrob; Animals; Starch; ženské pohlaví; Dietary Carbohydrates; Pan troglodytes; zvířata; dietní sacharidy